2009
DOI: 10.1590/s1809-29502009000400008
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da crioterapia e facilitação neuromuscular proprioceptiva sobre a força muscular nas musculaturas flexora e extensora de joelho

Abstract: As musculaturas flexora e extensora do joelho são freqüentemente lesionadas devido a um desequilíbrio entre esses grupos. Recursos térmicos, como a crioterapia, e técnicas de alongamento, como a técnica mantém-relaxa da facilitação neuromuscular proprioceptiva (FNP), influenciam a flexibilidade e força muscular, proporcionando maior homogeneidade entre essas musculaturas e diminuindo a incidência de lesões. Este estudo objetivou verificar os efeitos da crioterapia e da FNP sobre a força das musculaturas flexor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
6

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
1
6
0
6
Order By: Relevance
“…(14)(15)(16)(18)(19) Similar results were described in the study that linked the PNF in adolescents with hemiparesis to note the increase in muscle tone and postural corrections. (20) Based on statistical analysis, no significant differences were observed in the analyzed aspects of FIM, however clinically significant improvements were reported in the elderly parkinsonian functionality after the sessions based on the PNF.…”
Section: Discussionmentioning
confidence: 59%
“…(14)(15)(16)(18)(19) Similar results were described in the study that linked the PNF in adolescents with hemiparesis to note the increase in muscle tone and postural corrections. (20) Based on statistical analysis, no significant differences were observed in the analyzed aspects of FIM, however clinically significant improvements were reported in the elderly parkinsonian functionality after the sessions based on the PNF.…”
Section: Discussionmentioning
confidence: 59%
“…flexibility, as significant differences were found between assessments and reassessments for both techniques separately. In this same context, other studies comparing PNF to other methods showed that PNF led to greater increases in hamstring flexibility (26,27). In the same way, another study that compared static stretching to other techniques found that this method led to instant flexibility gains (28).…”
Section: Proprioceptive Neuromuscular Facilitation Stretching Protocolmentioning
confidence: 84%
“…Conforme apresentado na tabela 2, o aumento 21 ao analisarem a influência da crioterapia na flexibilidade e na força muscular da musculatura flexora e extensora do joelho, obtiveram como resultado a redução da força concên-trica imediatamente após a aplicação da crioterapia. Herbert e Noronha 4 demostraram que, após 30 minutos de resfriamento, ocorre aumento de força isométrica máxima imediatamente após a aplicação de frio, porém ao final do tratamento há um declínio na força muscular, sendo um fator negativo da aplicação de crioterapia.…”
Section: Resultsunclassified